El pensamiento político de Rafael Altamira - Ruiz Fernández, Rubén (Historiografías, 2023)
Rafael Altamira (1866-1951) was one of the foremost Spanish intellectuals of his time, having contributed to fields such as history, law and journalism. However, it would be wrong to separate his contributions to these fields from his political thought. This article offers an approach to his intellectual figure and political orientation at the limits of a liberal-progressive republican ideology, through the analysis of his texts and other secondary sources.KeywordsRafael Altamira, politics, liberalism, progressivism, republicanism